UNDERSTANDING YOUNG ENTREPRENEURS: INTEREST IN SUPPORTING BUSINESS SUCCESS - Retno Fuji Oktaviani (EKUITAS (Jurnal Ekonomi dan Keuangan), 2024)
Reducing unemployment is one of the complex economic development problems that is being faced by various countries, including Indonesia. Increasing awareness and entrepreneurial abilities, which are currently being carried out by the government, is a way to improve economic conditions and increase community potential. This research aims to determine how student interest can support business success by paying attention to personal factors that influence student personality: environment, motivation, and skills. The research respondents were Budi Luhur University students who had previously been entrepreneurs, totaling 209 respondents. This research uses the Structural Equation Model method with Partials Least Square. The research results show that interest can mediate motivation and skills on business success; apart from that, environmental factors are an essential determinant of increasing students' motivation to become entrepreneurs. High motivation is the main drive; skills are a strong foundation in managing a business, while deep interest is the driving factor that maintains active involvement and focus on business development. A balanced combination of these three factors is often the key to student entrepreneurial success, helping them face challenges and take advantage of opportunities in the dynamic business world.